ANALISIS COMMON SIZE UNTUK MENILAI KINERJA KEUANGAN PT INDOSAT TBK - Sriwiyanti, Eva; Saragih, Rai Fazran Nuarza (Jurnal Ilmiah Accusi, 2024)
The goal of this study is to use common size analysis to determine PT Indosat Tbk's financial performance within the 2020–2023. The quantitative method was used in this study. The information is taken from the 2020–2023 financial filings of PT Indosat Tbk. The common size analysis was used to examine the information in the income statement and statement of financial performance. The study's findings, which were derived from the balance sheet and profit and loss statement for the 2020–2023, show that the company's financial performance is improving, with the exception of the trend cash ratio analysis and current ratio, which show less favorable conditions.
Keywords: Financial Performance; Common Size Analysis